Reward Design for Customer Referral Programs: Reward–Product Congruence Effect and Gender Difference - Hu, Hai-hua; Zhang, Xin-Mu (Frontiers in Psychology, 2021)
Referral reward design is the core component of customer referral programs, which are often applied to recruit new customers. This research investigates the effectiveness of utilitarian vs. hedonic rewards in terms of referral generation. Through one field study and two laboratory studies, we demonstrate a reward–product congruency effect; that is, utilitarian rewards, compared with hedonic rewards, yield a higher referral likelihood for utilitarian products, while the opposite holds true for hedonic products. However, such a congruency effect would be crippled by gender segmentation. When males make referral decisions toward hedonic products, the effectiveness of utilitarian rewards is at least equal to that of hedonic rewards. When females make referral decisions toward utilitarian products, there is no difference in effectiveness between utilitarian and hedonic rewards. These findings provide novel insights into referral reward design.